Experimental addition of nitrogen to a whole forest ecosystem at Gårdsjön, Sweden (NITREX): Nitrate leaching during 26 years of treatment. (November 2018) - Moldan, Filip; Jutterström, Sara E.A-K.; Hruška, Jakub; Wright, Richard F.
Abstract: Chronic high deposition of nitrogen (N) to forest ecosystems can lead to increased leaching of inorganic N to surface waters, enhancing acidification and eutrophication. For 26 years nitrogen has been added as ammonium nitrate (NH4 NO3 ) at 40 kg N ha −1 yr −1 to a whole forested catchment ecosystem at Gårdsjön, Sweden, to experimentally simulate the transition from a N-limited to N-rich state. Over the first 10 years of treatment there was an increasing amount of nitrate (NO3 − ) and to a lesser extent ammonium (NH4 + ) lost in runoff, but then N leaching stabilised, and for the subsequent 16 years the fraction of N added lost in runoff remained at 9%. NO3 − concentrations in runoff were low in the summer during the first years of treatment, but now are high throughout the year. High frequency sampling showed that peaks in NO3 − concentrations generally occurred with high discharge, and were enhanced if high discharge coincided with occasions of N addition. Approximately 50% of the added N has gone to the soil. The added N is equivalent to 140 years of ambient N deposition. At current ambient levels of N deposition there thus appears to be no immediate risk of N saturation at this coniferous forest ecosystem, and by inference to other such N-limited forests in Scandinavia. Graphical abstract: Image 1 Highlights: Nitrate leaching increased for 10 yrs, but then flattened out to 4–16% of N inputs. High nitrate concentration episodes comes with high discharge, throughout the year. N additions have slowed recovery from reduced sulphur deposition. N additions have supressed leaching of DOC. Abstract : Nitrate leaching increased for 10 years, but then flattened out to 4–16% of N inputs with no further increase despite 16 more treatment years and >1000 kg N added.